Organizational Learning in a Cardiac Intensive Care Unit: A Learning History. Issue 2 (March 2017) - Lyman, Bret; Ethington, Kalene M.; King, Carly; Jacobs, Jonathan D.; Lundeen, Hayley
Abstract : Introduction: Providing high-quality care to every patient is challenging, particularly in critical care units (CCUs). However, this standard can be achieved through organizational learning. Unfortunately, the process of organizational learning in CCUs is not well understood. Objective: The objective of this study is to describe the developmental progression of a cardiac intensive care unit (CICU) to reach its current state of reliably excellent clinical performance. Methods: The method selected for this study was a learning history. A total of 43 individuals with experience working on the CICU participated in small group interviews. Participants included nurses, surgeons, unit clerks, administrators, nursing assistants, a pharmacist, a respiratory therapist, and an administrative assistant. Relevant artifacts, including unit performance data, were also gathered to complement interview data. Results: The CICU progressed through 4 distinct developmental stages to reach its current state. The CICU's early development involved establishing psychological safety on the unit, which prepared the unit for increased accountability, improved performance, and the pursuit of reliability. Discussion/Conclusion: The findings validate the relationship between psychological safety and organizational learning, offer insight into how CCUs become high-reliability organizations, and provide clinical leaders with guidance for achieving high reliability in their organizations. The findings also help validate the American Association of Critical-Care Nurses position that a healthy work environment is essential to achieving clinical excellence. Critical care unit teams should use these findings as a framework for collective reflection and planning to achieve their desired future. Further research is needed to validate the applicability of these findings and to continue building the evidence base for organizational learning in hospital units.